Biomarkers in Recurrent Grade III Glioma Patients Treated with Bevacizumab and Irinotecan. (7th February 2018) - Toft, Anders; Urup, Thomas; Christensen, Ib Jarle; Michaelsen, Signe Regner; Lukram, Babloo; Grunnet, Kirsten; Kosteljanetz, Michael; Larsen, Vibeke Andrée; Lassen, Ulrik; Broholm, Helle; Poulsen, Hans Skovgaard
ABSTRACT: Predictive biomarkers and prognostic models are required to identify recurrent grade III glioma patients who benefit from existing treatment. In this study of 62 recurrent grade III glioma patients, a range of clinical and paraclinical factors are tested for association with progression-free survival, overall survival, and response to bevacizumab and irinotecan therapy. Significant factors from univariate screening are included in multivariate analysis. Biomarkers previously advanced as predictive or prognostic in the first-line setting did not affect outcome in this patient cohort. Based on the optimized model for overall survival, comprising performance status and p53 expression, a prognostic index is established.